Consumer Preferences Towards Halal Product Purchase Decisions with Purchase Intention as a Mediating Variable - hismendi, hismendi; Nasir, Muhammad; Yazid AR, M. (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study explores the factors influencing halal product purchase decisions among the Muslim community in Lhokseumawe, with purchase intention acting as a mediating variable. The research is motivated by the growing demand for halal products and the need to understand consumer behavior in Muslim-majority regions. The main objective is to examine how product quality, halal assurance, price, and consumer trust affect both purchase intention and the final purchase decision. A quantitative method was employed, using a sample of 152 respondents selected through snowball sampling from a population of 188,888 Muslim residents. Data were analyzed using Structural Equation Modeling with a confirmatory approach. The findings indicate that product quality, halal assurance, price, and consumer trust all have a significant and positive impact on purchase intention. In turn, purchase intention significantly influences actual purchase decisions. Moreover, purchase intention effectively mediates the relationship between the influencing factors and the purchase decision. The study concludes that integrated marketing strategies emphasizing quality, price competitiveness, halal certification, and trust development are essential to strengthen consumer engagement and expand the halal product market in similar demographic settings.